Предмет: Алгебра,
автор: salodat652
5 Решите уравнение: a) (6-x)(x+6)-(x-11)x=36
Ответы
Автор ответа:
0
Ответ: 0. 5.5.
Объяснение:
(6-x)(x+6)-(x-11)x=36;
6x+36-x^2-6x - x^2+11x = 36;
- x^2-x^2 + 6x-6x+11x = 0;
-2x^2+11x-=0;
-x(2x-11) = 0;
x1=0;
x2 = 11/2 = 5.5.
Похожие вопросы
Предмет: Русский язык,
автор: danikkiselev79
Предмет: Кыргыз тили,
автор: Bozjigitovamengdi
Предмет: Другие предметы,
автор: margoshik10
Предмет: Математика,
автор: natalimilovanova004
Предмет: Математика,
автор: aminanabi40